ANALISIS KOMPOSISI KIMIA PRODUK PIROLISIS LAMBAT OFF-GRADE RUBBER PADA SUHU 300 °C - Agustina Tri Putri Sitinjak; RR Dirgarini Julia Nurlianti Subagyono; Veliyana Londong Allo; Ari Susandy Sanjaya (PROSIDING SEMINAR KIMIA, 2025)
This study was conducted to determine the yield and chemical composition of slow pyrolysis products of off-grade rubber at 300 °C. From the pyrolysis experiments, the yield of bio-oil was 28.25%. Analysis with Gas Chromatography-Mass Spectrometry showed that the bio-oil from off-grade rubber was mainly composed of γ-Elemene, 1H-Benzocycloheptene, octahydro-3,5,5-trimethyl-9-methylene-, (4aS-cis)-, 1,5-Cycloundecadiene, 8,8-dimethyl-9-methylene-, Geranyllinalool Isomer B, and Geranylgeraniol.   Keywords: Slow Pyrolysis, Off-grade Rubber, bio-oil, GC-MS